POLA SEBARAN KEJADIAN PENYAKIT PNEUMONIA PADA BALITA DI KECAMATAN BERGAS, KABUPATEN SEMARANG - Mia Sri Aulina; Mursid Rahardjo; Nurjazuli Nurjazuli (Jurnal Kesehatan Masyarakat (Undip), 2017)
Pneumonia is an infectious disease that causes death in children around the world. The discovery and treatment of pneumonia infants in Central Java in 2015 was 53.31%. In 2016 the discovery of infant pneumonia in Semarang District is the highest is Puskesmas Bergas that is as many as 346 cases of 3,828 children under five years. Risk factors that can cause pneumonia are environmental factors inside and outside the home. The purpose of this study was to analyze the pattern of the spread of pneumonia in under five years based on environmental factors and to see the relationship of pneumonia occurrence in infants with environmental factors in the house Bergas, Semarang District. The type of this research is observational analytics with case control design and sampling with purposive sampling technique. The number of samples in this study were all children under five years (0-59 months) who had a history of pneumonia from October 2016 to April 2017 of 102 respondents. Bivariate analysis using chi square test with significance value (α = 5%) showed that there was significant correlation between floor type (p-value 0,010) and fuel type (p-value 0,019) with pneumonia incidence in children under five years. Spatial analysis using Arcgis software 10.3. The pattern of spreading incidence of pneumonia in Bergas, Semarang District showed clustered pattern. The dominant patterns of environmental risk factors for pneumonia among children under five years are population density, healthy house coverage, industrial density and the presence of health services.